Nonaggressive and adapted social cognition is controlled by the interplay between noradrenergic and nicotinic receptor mechanisms in the prefrontal cortex. Issue 11 (23rd July 2013) - Coura, Renata S.; Cressant, Arnaud; Xia, Jing; de Chaumont, Fabrice; Olivo‐Marin, Jean Christophe; Pelloux, Yann; Dalley, Jeffrey W.; Granon, Sylvie
Abstract : Social animals establish flexible behaviors and integrated decision‐making processes to adapt to social environments. Such behaviors are impaired in all major neuropsychiatric disorders and depend on the prefrontal cortex (PFC). We previously showed that nicotinic acetylcholine receptors (nAChRs) and norepinephrine (NE) in the PFC are necessary for mice to show adapted social cognition. Here, we investigated how the cholinergic and NE systems converge within the PFC to modulate social behavior. We used a social interaction task (SIT) in C57BL/6 mice and mice lacking β2*nAChRs (β2 –/– mice), making use of dedicated software to analyze >20 social sequences and pinpoint social decisions. We performed specific PFC NE depletions before SIT and measured monoamines and acetylcholine (ACh) levels in limbic corticostriatal circuitry. After PFC‐NE depletion, C57BL/6 mice exhibited impoverished and more rigid social behavior and were 6‐fold more aggressive than sham‐lesioned animals, whereas β2 –/– mice showed unimpaired social behavior. Our biochemical measures suggest a critical involvement of DA in SIT. In addition, we show that the balance between basal levels of monoamines and of ACh modulates aggressiveness and this modulation requires functional β2*nAChRs. These findings demonstrate the critical interplay between prefrontal NE and nAChRs for the development of adapted and nonaggressive social cognition.—Coura, R. S., Cressant, A, Xia, J., de Chaumont, F., Olivo‐Marin, J. C., Pelloux, Y., Dalley, J. W., Granon, S. Nonaggressive and adapted social cognition is controlled by the interplay between noradrenergic and nicotinic receptor mechanisms in the prefrontal cortex. FASEB J . 27, 4343–4354 (2013). www.fasebj.org